"Passive Detection of Cutaneous Leishmaniasis in Police Personnel Deployed in the Provinces of Isfahan, Ilam, Bushehr, Khorasan and Khuzestan, Iran" - MR Jahani; MJ Gharavi; H Hadi Shirzad (Tehran University of Medical Sciences, 2003)
Leishmaniasis is a common parasitic disease in tropical and subtropical areas of the world. Police personnel deployed in the suburbs and rural areas are the most often exposed to the potential risk of cutaneous leishmaniasis. Furthermore, since the same police personnel are sent on duty to other places, their migrations can also play a considerable role in the transmission of this disease to their various destinations. In this study, the studied population comprises those patients referred to the police public health centers, in Isfahan, Ilam, Bushehr, Khorassan, and Khuzestan provinces from 1997 to 2001. The suspected individuals were counted as haring leishmaniasis after examination of the suspected lesions was confirmed by demonstring Leishman bodies in Geimsa stained smears that prepared them and/or culture in NNN media. The results showed altogether 610 cutaneous leishmaniasis (CL) cases confirmed by Leishman bodies' demonstration in suspected lesions and promastigotes forms in NNN media. The distribution of absolute and relative frequencies of CL were 288(47.2%), 155(25.0%), 96(15.7%), 54(8.7%) and 27 (4.3%) in Khorasan, Ilam, Khusestan, Isfahan and Bushehr provinces from 1997 to 2001 respectively.